OPTN/SRTR 2020 Annual Data Report: Heart. (10th March 2022) - Colvin, M.; Smith, J. M.; Ahn, Y.; Skeans, M. A.; Messick, E.; Bradbrook, K.; Gauntt, K.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
Abstract: As we enter the third year of the new adult heart allocation policy, we are faced with the new challenges of the COVID‐19 pandemic. In 2020, new listings (adult and pediatric) decreased slightly, with 4000 new listings in 2020, compared with 4087 in 2019; however, the number of adult heart transplants performed continued to increase, to 3715 in 2020. The number of pediatric heart transplants declined from 509 in 2019 to 465 in 2020. One‐year and six‐month posttransplant mortality rates in adult recipients have increased slightly since 2015 but have not significantly changed over the past decade. Overall, posttransplant mortality rates for adult recipients were 7.4% at six months and 9.4% at one year for transplants in 2019, 14.0% at three years for transplants in 2017, and 19.1% at five years for transplants in 2015. Although shorter‐term posttransplant mortality rates have slightly increased, there has been a steady downward trend in longer‐term mortality. Mortality rates for pediatric recipients were 5.7% at six months and 8.1% at one year for transplants in 2019, 11.6% at three years for transplants in 2017, and 15.2% at five years for transplants in 2015.